An Ovine Model of Awake Veno-Arterial Extracorporeal Membrane Oxygenation - Qi, Jiachen; Gao, Sizhe; Liu, Gang; Yan, Shujie; Zhang, Min; Yan, Weidong; Zhang, Qiaoni; Teng, Yuan; Wang, Jian; Zhou, Chun; Wang, Qian; Ji, Bingyang (Frontiers in Veterinary Science, 2021)
Background: Large animal models are developed to help understand physiology and explore clinical translational significance in the continuous development of veno-arterial extracorporeal membrane oxygenation (VA-ECMO) technology. The purpose of this study was to investigate the establishment methods and management strategies in an ovine model of VA-ECMO. Methods: Seven sheep underwent VA-ECMO support for seven days by cannulation via the right jugular vein and artery. The animals were transferred into the monitoring cages after surgery and were kept awake after anesthesia recovery. The hydraulic parameters of ECMO, basic hemodynamics, mental state, and fed state of sheep were observed in real time. The blood gas analysis and activated clotting time (ACT) were tested every six hours, while the complete blood count, blood chemistry, and coagulation tests were monitored every day. Sheep were euthanized after seven days. Necropsy was performed and main organs were removed for histopathological evaluation. Results: Five sheep survived and successfully weaned from ECMO. Two sheep died within 24–48 h of ECMO support. One animal died of fungal pneumonia caused by reflux aspiration and the other died of hemorrhagic shock caused by bleeding at left jugular artery cannulation site used for hemodynamic monitoring. During the experiment, hemodynamics of the five sheep were stable. The animals stayed awake and freely ate hay, feed pellets, and drank water. With no need for additional nutrition support or transfusion, hemoglobin concentration and platelet count were in the normal reference range. ECMO flow remained stable and the oxygenation performance of the oxygenator was satisfied. No major adverse pathological injury occurred. Conclusions: The perioperative management strategies and animal care are the key point of the VA-ECMO model in conscious sheep. This model could be a platform for further research of disease animal models, pathophysiology exploration, and new equipment verification.